2019
DOI: 10.1111/pbi.13305
|View full text |Cite|
|
Sign up to set email alerts
|

Cytokinin dehydrogenase: a genetic target for yield improvement in wheat

Abstract: J.S.)) and (Tel +64 275553582; email paula.jameson@canterbury.ac.nz (P.E.J.)) SummaryThe plant hormone group, the cytokinins, is implicated in both qualitative and quantitative components of yield. Cytokinins have opposing actions in shoot and root growth-actions shown to involve cytokinin dehydrogenase (CKX), the enzyme that inactivates cytokinin. We revise and provide unambiguous names for the CKX gene family members in wheat, based on the most recently released wheat genome database, IWGSC RefSeq v1.0 & v2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
146
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(151 citation statements)
references
References 127 publications
(217 reference statements)
4
146
1
Order By: Relevance
“…None exhibits the same role in the GC and in the field. Zhang et al [ 35 ] reported that TaCKX6 , renamed by [ 20 ] as TaCKX2.2.1-3D , is an orthologue of OsCKX2 regulating rice yield [ 10 ]. The cultivar, which has an 18-bp deletion, showed decreased expression of this gene, which was associated with a greater TGW than in other haplotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None exhibits the same role in the GC and in the field. Zhang et al [ 35 ] reported that TaCKX6 , renamed by [ 20 ] as TaCKX2.2.1-3D , is an orthologue of OsCKX2 regulating rice yield [ 10 ]. The cultivar, which has an 18-bp deletion, showed decreased expression of this gene, which was associated with a greater TGW than in other haplotypes.…”
Section: Discussionmentioning
confidence: 99%
“…TaCKX2 underwent gene duplication [ 15 ] and the resultant genes were assigned as TaCKX2.1 and TaCKX2.2 based on the Ensembl Plants database [ 19 ] and phylogenetic analysis by Ogonowska et al [ 16 ]. The numbering of TaCKX GFMs was recently revised taking advantage of the most up-to-date databases (including IWGSC RefSeq v2.0), their homology with closely related monocot species including barley and diploid genome specificity [ 20 ]. Based on these data, there are 13 TaCKX GFMs basically numbered as TaCKX1 , TaCKX2.1 , TaCKX2.2.1 , TaCKX2.2.2 , TaCKX2.2.3 , TaCKX3 ( 6 ), TaCKX4 , TaCKX5 , TaCKX7 , TaCKX8 ( 11 ), TaCKX9 ( 10 ), TaCKX10 ( 9 ) and TaCKX11 ( 3 ), and 12 of them are allocated to each of the three chromosomes associated with the A, B and D genomes, giving the number of 35 homoeologous genes.…”
Section: Introductionmentioning
confidence: 99%
“…The other important component of CK metabolism is the CKX enzyme, which accounts for the irreversible inactivation of CKs by cleaving the side chain from CK molecules [46]. Genome-wide association studies have recently shed more light on the potential function of CKX members in plant species, with 13 CKX GFMs in maize [71], 11 CKX GFMs in rice [66], 12 CKX GFMs in apple [67], CKX GFMs in wheat (Triticum aestivum) [72] and 23 CKX GFMs in rapeseed (Brassica napus) [73]. Increasing lines of evidence suggest that CKX GFMs play important roles in various plant physiological and developmental modifications under drought stress [74][75][76] (Table 1).…”
Section: Response Of Ck Metabolic Genes To Droughtmentioning
confidence: 99%
“…We documented that both tZ and cZ, which are isomers of zeatin, together with their derivatives are a major group of isoprenoid CKs in 7 DAP spikes. It has already been shown that trans-zeatin is the predominant form after anthesis (Morris et al 1993, Hess et al 2002), but comprehensive analysis of cytokinins during spike, spikelet, ovule and grain development has not yet been reported for wheat using LC-MS/MS (Chen et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…TaCKX6a02 was annotated as TaCKX2.1 , TaCKX6-D1 (JQ797673) was annotated as TaCKX2.2 and TaCKX2.4 was annotated as TaCKX2.2 . Annotations for these genes were maintained in the recently published review on the TaCKX (Chen et al 2019), however tested in this research TaCKX10 was renamed as TaCKX9 and TaCKX3 was renamed as TaCKX11 . Newly revised by Chen et al (2019) naming is applied and former names are in brackets.…”
Section: Introductionmentioning
confidence: 99%